P3.106 Uptake of home-based point-of-care syphilis & hiv testing among male partners of pregnant women in western kenya. (8th July 2017) - Mark, Jennifer; Kinuthia, J; Roxby, A; Krakowiak, D; Osoti, A; Richardson, B; Ma, Gone; Asila, V; Parikh, S; Farquhar, C
Abstract : Introduction: Few men are tested for syphilis or HIV during their partners' pregnancy, a period of high HIV transmission risk and preventable adverse pregnancy outcomes. Offering home-based STI education and point-of-care (POC) testing of syphilis to couples can support HIV programs to reduce transmission of sexually transmitted infections and adverse pregnancy outcomes. Methods: We assessed male partner uptake of paired POC syphilis and HIV tests within a randomised controlled trial (RCT) of 600 pregnant women and their male partners in Kenya. Married or cohabiting women were unaccompanied and attending a clinic-based first antenatal visit at recruitment. Participating men received a couple home-based visit with testing during pregnancy or at 6 months postpartum. We also evaluated whether the addition of syphilis testing has an effect on the uptake of HIV testing among men. Results: From September 2013 to June 2014, male participation in home-based visits was 85% among women remaining enrolled (260 during pregnancy, 240 postpartum). Paired testing was offered to subsets of 80 and 230 men during pregnancy and postpartum. In both groups, test uptake was high: 1) For syphilis, 91% men agreed to test during pregnancy and 96% agreed postpartum; 2) For paired syphilis and HIV testing, 91% of men tested for both during pregnancy and 98% tested postpartum. Third, adding syphilis testing did not adversely affect home-based male partner HIV testing during pregnancy among 260 men, as HIV test uptake was 96% before (of 180), 95% after (of 80) syphilis test introduction, and remained 2-times greater than clinic-based HIV testing alone within the RCT (39%). Finally, men intended to seek clinic treatment if they received a positive test result during pregnancy and postpartum (94% and 95%, respectively). Conclusion: Men were likely to accept both syphilis and HIV tests when offered at home without adversely affecting HIV testing approaches. POC diagnostics can work well outside facilities and increase testing of male partners who rarely accompany women to antenatal clinics.